1996
DOI: 10.1002/j.1460-2075.1996.tb00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental elongation of telomeres extends the lifespan of immortal x normal cell hybrids.

Abstract: Hybrids between immortal cells that express telomerase and normal cells that lack telomerase have a limited lifespan. We demonstrate that telomerase is repressed in such hybrids. Treatment of immortal human cell lines with certain oligonucleotides resulted in telomere elongation. We took advantage of this observation to test the hypothesis that elongation of telomeres would extend the lifespan of cells in culture. An immortal human cell line was treated with an oligonucleotide to lengthen its telomeres and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
2
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 58 publications
6
87
2
2
Order By: Relevance
“…This activation is dependent on wtp53. Elongation of telomeres after the treatment of immortal cells with G-rich oligonucleotides was also shown in another study (Wright et al, 1996). However, the p53 status of the cell lines examined was not mentioned, nor was whether or not the cells went through a temporary block of proliferation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This activation is dependent on wtp53. Elongation of telomeres after the treatment of immortal cells with G-rich oligonucleotides was also shown in another study (Wright et al, 1996). However, the p53 status of the cell lines examined was not mentioned, nor was whether or not the cells went through a temporary block of proliferation.…”
Section: Discussionmentioning
confidence: 67%
“…Unsynchronized cells were treated daily with oligonucleotides (BioTez Berlin, Germany) in concentrations as indicated for up to 6 consecutive days. The half-life of these oligonucleotides in serum-supplemented medium has been estimated to be 4 ± 6 h (Wright et al, 1996). For some experiments cells were partially synchronized by con¯uence.…”
Section: Chemicals and Treatmentsmentioning
confidence: 99%
“…Complementation studies of somatic cell hybrids (Pereira-Smith and Smith, 1988) have demonstrated that some immortal6immortal cell fusions may still senesce depending on the cell combinations used and that all mortal6immortal hybrids senesce suggesting that mortality is a dominant trail (Karlsson et al, 1996;Wright et al, 1996). In addition, several studies of cellular senescence induced by microcell chromosome mediated fusion have been reported (Barrett, 1993;Ohmura et al, 1995;Saski et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Consistently, elongation of telomeres extends the life span of cells in culture. 9 Taken together, immortal cells have to maintain telomere length to continue proliferation, mainly by reactivation of telomerase. 10 Telomerase activity was detected in approximately 85% of various types of cancers including HCC by the telomeric repeat amplification protocol (TRAP), [11][12][13][14][15][16][17] a sensitive assay, whereas most normal somatic cells did not exhibit the activity.…”
mentioning
confidence: 99%